Statin use and risk of tuberculosis: a systemic review of observational studies - Haizhen Duan; Tongying Liu; Xiaojun Zhang; Anyong Yu; Yu Cao (International Journal of Infectious Diseases, 2020)
Objectives: Statin intake may be linked with a lower risk of several infectious diseases, including tuberculosis, which is an important cause of mortality worldwide. The aim of this study was to investigate the definite impacts of statins on the risk of tuberculosis (TB) in diabetic patients and in the general population. Methods: Four databases were thoroughly searched from inception up to July 2019. Articles in any language were included if they assessed and clarified statin intake, presented the risk of TB in diabetes mellitus (DM) patients or the general population, and reported odds ratios (ORs), relative risks (RRs), or hazard ratios (HRs) or contained data for relevant calculation. RRs with 95% confidence intervals (CIs) were pooled using random-effects models regardless of heterogeneity quantified by Cochran’s Q and I2 statistics. Results: Six articles reporting observational studies involving 2 073 968 patients were included. Four reported cohort studies, one a nested case–control study, and one was an abstract. Statin use significantly reduced the risk of TB in DM patients by 22% (pooled RR 0.78, 95% CI 0.63–0.95), with severe heterogeneity (I2 = 76.1%). Statin intake also significantly decreased the risk of TB in the general population by 40% (pooled RR 0.60, 95% CI 0.50–0.71), with severe heterogeneity (I2 = 57.7%). Conclusions: Statin use is related to a considerably lower risk of TB in both DM patients and the general population. However, these conclusions should be interpreted with caution given the possible remaining confounding, and call for large-size and multicenter randomized controlled studies in the future. Keywords: Statins, Tuberculosis, Diabetes mellitus, Risk, Systemic review